The Impact of Workaholism on Employees’ Work-Life Imbalance - Wolor, Christian Wiradendi; Ardiansyah; Rofaida, Rofi; Nurkhin, Ahmad; Ali Rababah, Mahmoud Ali Rababah (Jordan Journal of Business Administration, 2025)
This study examines the impact of workaholism on employees’ work-life imbalance and its relationship with their job satisfaction and stress, especially during COVID-19. The study uses a quantitative approach with structural equation modeling (SEM) to analyze data. The population of this study consisted of Jakarta employees engaged in the financial sector with a total sample of 203 people. The data was collected throughout April-August 2022. The results showed that workaholism does not affect work-life imbalance (b = 0,00, p = 0.00), work stress (b = -0.33, p = -0.03), or job satisfaction (b = -0.19, p = -0.20). The work-life imbalance affects work stress (b = 0.77, p = 0.77), does not affect job satisfaction (b = 0.20, p = 0.00), whereas work stress affects job satisfaction (b = 0.20, p = 0.00). The study’s findings revealed that employees are not overburdened with work, because work-life imbalance, work stress, and job satisfaction remain unaffected. The study recommends that organizations create programs to transform this sense of imbalance into work-life balance, reduce stress, and increase job satisfaction.